Pelatihan Digital Marketing Bagi UMKM di Danukusuman Surakarta - Yuni Pristiwati Noer Widianingsih; Prijanto, Tulus; Santosa, Slamet; Syukriyana, Dzikriya; Zai, Simon; Nurkhayati, Eko; Sukmajati, Amru (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
This training was intended for Small and Medium Enterprises (SMEs) in Danukusuman Surakarta. It aims to improve SMEs' basic understanding of digital marketing, introduce SMEs to various digital marketing tools, provide practical skills in using digital media for promotion, and encourage business actors to start utilizing online platforms optimally. The activity results showed that participants were enthusiastic about participating in the training They received training materials from the basics and were able to directly practice the material that had been taught about the basic concepts of digital marketing, the benefits, and the differences with conventional marketing. They can practice directly with their products by taking pictures of their respective products and getting direct feedback. This digital marketing training is very helpful for SMEs to prepare themselves to face challenges in the digital era. As long as the training activities show that the participants respond well, the material provided is practical and can be applied directly by SMEs, which can motivate SMEs to develop their businesses online.